Farm to School Activities and Student Outcomes: A Systematic Review. Issue 2 (5th September 2019) - Prescott, Melissa Pflugh; Cleary, Rebecca; Bonanno, Alessandro; Costanigro, Marco; Jablonski, Becca B R; Long, Abigail B
ABSTRACT: Farm to school programs (F2SPs) operate in 42% of school districts and are supported in part through federal and state policies as well as philanthropic funding. Although research evaluating the effects of farm to school–related activities on student outcomes is growing, a systematic review of the results and thus a synthesis of implications for future programming have not occurred. The primary objective of this systematic literature review is to summarize and evaluate studies on student outcomes associated with farm to school–related activities up to 1 September, 2017. Four databases spanning 4 research disciplines were used to identify full-text, English-language studies. Twenty-one studies were reviewed: 7 explicitly investigated F2SPs, and 14 evaluated the impact of school-based interventions that were relevant to activities reported in the 2013 and/or 2015 Farm to School Census. All of the F2SP studies ( n = 7) and 85.7% of farm to school–related activity studies ( n = 12) were multicomponent, and there was a wide variety of implemented intervention components across the reviewed studies. Results from F2SP and farm to school–related activity studies consistently show positive impacts on food and nutrition-related knowledge; most studies also suggest a positive relation between farm to school–related activities and healthy food selection during school meals, nutrition self-efficacy, and willingness to try fruits and vegetables. The impact of farm to school activities on fruit and vegetable consumption and preferences is unclear. The most common F2SP study limitations were study designs that preclude causal inference, outcome measurement with no reported or limited psychometric testing, lack of long-term outcome evaluation, and challenges related to quantifying intervention implementation. These findings underscore the need for more conclusive evidence on the relation between farm to school–related activities and changes in fruit and vegetable consumption.